Disease extent and antitubercular treatment response correlates with Mycobacterium tuberculosis specific CD4 Tcell phenotype regardless of HIV1 status - Riou,C; Du,Bruyn E; Ruzive,S; Goliath,RT; Lindestam,Arlehamn CS; Sette,A; Sher,A; Barber,DL; Wilkinson,RJ (Clinical & Translational Immunology, 2020)
ObjectivesThe development of nonsputumbased assays for tuberculosis (TB) diagnosis and treatment monitoring is a key priority. Recent data indicate that whole bloodbased assays to assess the phenotype of Mycobacterium tuberculosis (Mtb)specific CD4 T cells hold promise for this purpose and require further investigation in wellcharacterised TB cohorts. In this study, we investigated the relationship between the phenotypic signature of Mtbspecific CD4 responses, TB disease extent and treatment response.MethodsUsing flow cytometry, we measured the expression of phenotypic and functional markers (HLADR, CD27, CD153, KLRG1, IL2, MIP1β, TNFα and IFNγ) on Mtbspecific CD4 Tcells in whole blood from 161 participants of varying TB and HIV status. TB disease extent was graded as a continuum using the Xpertct value, Creactive protein, Timika radiographic score and monocyte/lymphocyte ratio.ResultsThe phenotypic profile of Mtbspecific CD4 T cells preantitubercular treatment (ATT) strongly correlated with disease extent, irrespective of HIV status. ATT associated with major changes in the phenotype of Mtbspecific CD4 T cells, with decreased expression of HLADR and increased CD27 and CD153 expression. Principal component analysis showed an almost complete separation between latent TB infection (LTBI) and active TB (aTB) preATT groups, whereas the profile of the aTB postATT group overlapped with the LTBI group. However, in patients experiencing treatment failure or relapse, no significant changes were observed in Mtbspecific CD4 Tcell phenotype pre and postATT.ConclusionWhole bloodbased assays of Mtbspecific CD4 Tcell activation and maturation markers can be used as nonsputumbased biomarkers of disease extent and treatment monitoring in TB, regardless of HIV1 status.